Valorisation of hazardous medical waste using steam injected plasma gasifier: a parametric study on the modelling and multi-objective optimisation by integrating Aspen plus with RSM. Issue 27 (6th December 2022) - Singh, Deepak Kumar; Tirkey, Jeewan V.
ABSTRACT: The COVID-19 Pandemic has a detrimental effect on the environment related to the exponential rise in medical waste (MW). Extraction of energy from the toxic MW with the latest gasification technology instead of conventional incineration is of utmost importance to promote sustainable development. This present study investigates the processing of MW for the generation of enriched hydrogen syngas using steam injected plasma gasifier. Modelling of Plasma gasifier was performed in Aspen Plus and Model validation was done with the experimental result and, a good agreement was attained. Sensitivity analysis was implemented on MW in which the influence of gasification temperature, equivalence ratio (ER), and Steam/Biomass (S/B) on the producer gas (PG) composition, gas yield, H2 /CO ratio, cold gas efficiency (CGE), and the higher heating value (HHV) was calculated. Furthermore, Response surface methodology (RSM) has been incorporated for the multi-objective optimisation of the variable gasification parameters. R 2 values obtained from ANOVA for H2, CGE, and HHV are 98.62%, 99.10%, and 98.9% respectively. Using the response optimiser, the optimum values of H2, CGE, and HHV were found to be 0.43 (mole frac), 89.95%, and 7.49 MJ/Nm 3 for temperature at 1560.60°C, equivalence ratio 0.1, and S/B 0.99, respectively. The observed coefficient of desirability was about 0.97. GRAPHICAL ABSTRACT: UF0001